Ang Tatay kong nanay - Nadres, Orlando; Batac, Jose; Lahad, Lutgardo; Dolphy; Muhlach, Nino; Salvador, Philip; Delgado, Marissa; Villanueva, Lorli; Brocka, Lino; Yu, Jesus B.; Salvador, Augusto (Lotus Films], 1976)
Dolphy stars with Nino Muhlach in a drama about a gay who brings up a young boy as his own son.